Factors Influencing Muslim Consumer’s Satisfaction and Loyalty of Restaurant in Yogyakarta, Indonesia - Sumadi (Journal of Islamic Economics Lariba, 2022)
The objective of this study is to investigate the factors that affect Muslim customers' satisfaction and loyalty in Yogyakarta, Indonesia. Customers of restaurants in Yogyakarta are all Muslims. Non-probability sampling was administered to collect data and total of 120 questionnaires were collected. Questionnaires were delivered directly to the target respondents both in person and online by employing a Google form. The Statistical Equation Modeling (SEM) statistical analysis tool, available in IBM® SPSS® Amos, was administered to determine the data. The study's findings demonstrate that customer satisfaction is positively and significantly influenced by product quality, service quality, and halal certification. In addition to that, customer loyalty is significantly influenced by customer satisfaction. Customer loyalty is directly impacted by factors such as product quality and service quality, but halal certification does not possess a positive or significant direct impact on loyalty. Halal assurance must pass through the satisfaction intervening variable before having an impact on loyalty.